Mild Hybrid Electro-Thermal Battery Modelling - Biswas, Akik; Yao, Xuming (My University, 2016)
In this thesis an electro-thermal battery pack model has been developed for a 48 V Mild Hybrid vehicle application to predict the pack temperature under different loading cases which have been verified with experiments. Both the joule and the entropic heat play significant roles in the total heat generation process. Furthermore, the entropic heat can be both endothermic and exothermic and these processes have also been verified. The contribution of entropic heat to the thermal dynamic behavior was verified through simulations using GTSUITE software and experiment. For the electrical battery pack model it was found that the 2 RC circuit model captured the electrical dynamic behavior which was in good agreement with the experiment data, whereas the 0 RC circuit model failed to do so. The 2 RC circuit model produced an error of 1.5 %, whereas the 0 RC circuit model gave an error of 3.2 %. Experiments were carried out both at the battery pack for temperature measurements and at the cell level to determine the internal battery cell parameters such as R0, R1, R2, C1, C2, specific heat and the entropic heat. Moreover, the experiments were carried out over a wide range of state of charge (SOC) levels and temperatures restricted between 5 C and 45 C.
Keywords: Elkraftteknik; Electric power engineering